Pengaruh Rapat Arus dan Waktu Pelapisan Nikel pada AISI 410 dengan Metode Pulse Electrodeposition terhadap Strukturmikro dan Laju Korosi [The Influences of Current Density and Time on Microstructure and Corrosion Rate Nickel Coating in Aisi 410 by Pulse Electro Deposition Method] - Rivaldo Ramadhana Saputra; Soesaptri Oediyani; Yulinda Lestari; Efendi Mabruri (National Research and Innovation Agency (BRIN), 2017)
Nickel plating process with pulse methods in AISI 410 electrodepostion has been done to reduce corrosion rate of this material in industrial applications i.e turbine blade that is often experienced corrosion problems. The coating process using nickel sulfate 250 g / l, boric acid 50 g / l and nickel chloride 45 g / l at temperature of 50-60 ° C with various of current densities for 10, 15, 20 and 25 A / dm² and time for coating process of 10, 15 and 20 minutes. Duty cylce used was 80% and the pulse frequency approximately around 100 Hz. Microstructure examined by using SEM-EDS (scanning electron microscopy-energy dispersive spectroscopy) to observe grain size and thickness of the nickel layer. Corrosion rate measured by using CMS (corrosion measurement system). The results showed that increasing of current density and coating process would reduce grain size and corrosion rate in coating area. The corrosion rate is 0.00027 mmpy when the current density is 25 A / dm² and plating time is 20 minutes. AbstrakProses pelapisan nikel dengan metode pulse electrodepostion pada AISI 410 dilakukan untuk menurunkan laju korosi AISI 410 pada aplikasi industri, yaitu turbin blade yang sering mengalami masalah korosi. Proses pelapisan menggunakan larutan nickel sulphate 250 g/l, boric acid 50 g/l dan nickel chloride 45 g/l pada temperatur 50 – 60°C dengan variasi rapat arus 10, 15, 20 dan 25 A/dm² dan lamanya proses pelapisan 10, 15 dan 20 menit. Duty cylce yang digunakan adalah 80% dan frekuensi pulse 100 Hz. Pengujian struktur mikro dilakukan menggunakan SEM-EDAX untuk melihat ukuran butir dan ketebalan lapisan nikel yang terbentuk. Pengujian laju korosi dilakukan menggunakan alat CMS. Hasil penelitian menunjukkan bahwa semakin besar rapat arus dan semakin lama proses pelapisan maka ukuran butir yang tergambarkan dalam mikrostruktur lapisan semakin kecil dan laju korosi yang terukur semakin kecil. Laju korosi paling kecil adalah 0,00027 mmpy pada rapat arus 25 A/dm² dan waktu pelapisan 20 menit.